Efficacy of Scalp Cooling in Preventing and Recovering From Chemotherapy-Induced Alopecia in Breast Cancer Patients: The HOPE Study - Kinoshita, Takayuki; Nakayama, Takahiro; Fukuma, Eisuke; Inokuchi, Masafumi; Ishiguro, Hiroshi; Ogo, Etsuyo; Kikuchi, Mari; Jinno, Hiromitsu; Yamazaki, Naoya; Toi, Masakazu (Frontiers in Oncology, 2019)
Purpose: This study aimed to assess the efficacy of scalp-cooling devices in preventing chemotherapy-induced alopecia in Japanese breast cancer patients and investigate whether a scalp-cooling device improves hair volume recovery over a 12 weeks period after completing chemotherapy. Methods: This multicenter controlled trial included women with breast cancer undergoing chemotherapy in Japan between February 2016 and March 2018. The primary endpoint was the proportion of patients with no alopecia at the end of chemotherapy. The secondary endpoint included hair volume at 12 weeks after completing chemotherapy. Results: A total of 48 patients were enrolled; of them, 34 and 14 were sequentially allocated to the scalp-cooling group using the Paxman Hair Loss Prevention System and the control group, respectively. There was no significant difference in average age between the scalp-cooling and the control groups (50.0 ± 9.6 vs. 49.0 ± 9.0 years). More than 50% of patients in each group had stage II breast cancer (scalp-cooling group: 53.1%; control group: 64.3%), more than 90% received adjuvant chemotherapy (scalp-cooling group: 96.9%; control group: 92.9%), and more than 60% were treated with a docetaxel/cyclophosphamide regimen (scalp-cooling group: 75.0%; control group: 64.3%). There were more patients judged to have no alopecia at the end of chemotherapy in the scalp-cooling group than in the control group (26.7% [8/30] vs. 0% [0/13]; P = 0.011). The proportion of patients with alopecia who experienced an increase in hair volume of ≥50% within 12 weeks duration after chemotherapy was 85.7% (24/28) in the scalp-cooling group and 50.0% (6/12) in the control group. No patient developed serious adverse events related to the scalp-cooling device. Conclusions: The use of a scalp-cooling device prevented alopecia with acceptable safety for Japanese patients. In addition, scalp cooling resulted in faster recovery of hair volume after chemotherapy, even in patients for whom scalp cooling failed to prevent chemotherapy-induced alopecia.